1998
DOI: 10.1086/301920
|View full text |Cite
|
Sign up to set email alerts
|

A European Multicenter Study of Phenylalanine Hydroxylase Deficiency: Classification of 105 Mutations and a General System for Genotype-Based Prediction of Metabolic Phenotype

Abstract: Phenylketonuria (PKU) and mild hyperphenylalaninemia (MHP) are allelic disorders caused by mutations in the gene encoding phenylalanine hydroxylase (PAH). Previous studies have suggested that the highly variable metabolic phenotypes of PAH deficiency correlate with PAH genotypes. We identified both causative mutations in 686 patients from seven European centers. On the basis of the phenotypic characteristics of 297 functionally hemizygous patients, 105 of the mutations were assigned to one of four arbitrary ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
324
2
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(352 citation statements)
references
References 30 publications
17
324
2
9
Order By: Relevance
“…In contrast to its proven scientific value, the test has only limited value for the dietetic treatment of patients with classic and mild PKU because the Phe 72 value will not predict the current and future individual dietary requirements (see below) and the patients may manifest during the test signs of intoxication such as nausea, vomiting, irritability, insomnia and EEG changes. The test is no longer necessary [37] and has been replaced in practice by predictive molecular and enzymatic classifications [22,38]. A recent online survey accordingly revealed that only 4% of centers still use it for estimating the phenotype of their patients [23].…”
Section: Deficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to its proven scientific value, the test has only limited value for the dietetic treatment of patients with classic and mild PKU because the Phe 72 value will not predict the current and future individual dietary requirements (see below) and the patients may manifest during the test signs of intoxication such as nausea, vomiting, irritability, insomnia and EEG changes. The test is no longer necessary [37] and has been replaced in practice by predictive molecular and enzymatic classifications [22,38]. A recent online survey accordingly revealed that only 4% of centers still use it for estimating the phenotype of their patients [23].…”
Section: Deficiencymentioning
confidence: 99%
“…More precisely, PAH deficiency may be classified into four different phenotypes: classic PKU presenting with Phe pretreatment levels N1200 μmol/L, moderate PKU with Phe pretreatment levels of 900-1200 μmol/L, mild PKU with Phe pretreatment levels of 600-900 μmol/L, and mild HPA with Phe pretreatment level b600 μmol/L [38,39].…”
Section: Blood Phenylalaninementioning
confidence: 99%
See 2 more Smart Citations
“…The most common Turkish mutations, L48S and IVS10-11G>A, were present on 1.5 % and 2.6 % of German PKU chromosomes in Southern Germany and on 3. Clinical severity :"assigned value" (AV) of individual mutations (Guldberg et al, 1998 Clinical severity :"assigned value" (AV) of individual mutations (Guldberg et al 1998). AV=1, mutations causing severe PKU; AV=2, mutations causing moderate PKU; AV=4, mutations causing mild PKU; AV=8; mutations causing MHP 1 Other mutations that were found on single chromosomes (relative frequency 1.3 %): IVS4+5G>T, IVS4-5C>G, R241H, R243L, A300S, T380M, V388M, R408W, IVS12+1G>A. a Novel mutation.…”
Section: Resultsmentioning
confidence: 99%